Positive functions of socialisation and the development of social relations in ice hockey - Kuzmenko, A.A.; Stolyarov, V.I.; Kuzmenko, G.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to characterise the prerequisites for the realisation of the positive functions of socialisation and the development of social relations in ice hockey. Methods and structure of the study. Analysis of the literature, pedagogical observation, questionnaire survey, testing, correlation and factor analysis, interpretation. The series of studies were conducted on a contingent of hockey players from 2022 to 2025 at the following stages: initial preparation and training – National Hockey Center, Moscow; the stage of higher sports mastery – Saint Petersburg. Results and conclusions. The following were revealed: the factor weights of the qualities and abilities relevant in hockey – the criteria of the intellectual and motor adequacy to the social situation of development within the contours of the conjugated interaction of scientific approaches; the resources of the mutual complementation of effective game actions by hockey players under conditions of cooperation with partners and competitive counteraction to the opponent; the characteristic features of the socio-cultural influence of ice hockey on the social development of the personality.